COVID-19, Social Media, and the Role of the Public Physician - Topf, Joel M. (Blood Purif, 2021)
The COVID-19 pandemic has resulted in an avalanche of information, much of it false or misleading. Social media posts with misleading or dangerous opinions and analyses are often amplified by celebrities and social media influencers; these posts have contributed substantially to this avalanche of information. An emerging force in this information infodemic is public physicians, doctors who view a public presence as a large segment of their mission. These physicians bring authority and real-world experience to the COVID-19 discussion. To investigate the role of public physicians, we interviewed a convenience cohort of physicians who have played a role in the infodemic. We asked the physicians about how their roles have changed, how their audience has changed, what role politics plays, and how they address misinformation. The physicians noted increased audience size with an increased focus on the pandemic. Most avoided confronting politics, but others found it unavoidable or that even if they tried to avoide it, it would be brought up by their audience. The physicians felt that confronting and correcting misinformation was a core part of their mission. Public physicians on social media are a new occurrence and are an important part of fighting online misinformation.